Marker assisted introgression of broad spectrum blast resistance gene Pi-2 into an elite rice cultivar, Samba Mahsuri - Kumar, S Vijay; Prasad, M Srinivas; Rambabu, R; Bhaskar, B; Sundaram, R M; Ladhalakshmi, D; Laha, G S; Madhav, M Sheshu (Indian Journal of Plant Protection, 2020)
Rice blast disease is caused by fungal pathogen Pyricularia oryzae is one of the most devastating crop disease worldwide and its effects on rice production up to 70-80% in favourable conditions. In recent years, the rice scientists mainly concentrated on to develop new varieties for increasing production and productivity of rice with durable resistance to abiotic and biotic stress. In present study, broad spectrum rice blast resistant gene Pi-2 originating in the isogenic line C101A51 was incorporated into an elite cultivar ‘Samba Mahsuri (BPT 5204)’, which is highly susceptible to blast disease through one of the trendy breeding programme i.e., Marker Assisted Introgression (MAI). It involved backcross and selfing, at each backcross foreground selection was carried out by using gene specific linked marker MSM1. As a result, background selection was done by using a set of 61 parental polymorphic SSR markers spread across the rice genome. At BC1F1 a single plant possessing targeted gene Pi-2 along with maximum recovery of recurrent parent genome (~ 75.40%; plant # BA-23-11) was selected and advanced through selfing and ancestry-based selection for agro-morphological traits. Results confirmed that, resistance gene Pi-2 was successfully incorporated into recurrent parent Samba Mahsuri and three lines, viz., BA-23-11-89-12-56, BA-23-11-89-12-96 and BA-23-11-89-12-168 were identified at BC2F4 which are possessing high level of resistance against blast disease with high virulent of P. oryzae isolate (IIRR MSP-28). The agronomical traits of ‘ABL’s’ were very similar to those of the recurrent parent Samba Mahsuri. One ABL (BA-23-11- 89-12-96; ~ 93.40%) was found to be better than recurrent parent Samba Mahsuri (BPT 5204) regarding resistance and yield. The application of MAI is very useful to develop blast resistant variety with highest recovery of recurrent parent genome and also to reduce number of generations and time.